A qualitative analysis of loss-related memories after cancer loss: a comparison of bereaved people with and without prolonged grief disorder - Smith, KV; Rankin, H; Ehlers, A (Taylor & Francis, 2020)
Objective: The study aimed to explore the content and features of loss-related memories in a sample of individuals bereaved by cancer with and without a probable diagnosis of prolonged grief disorder/persistent complex bereavement disorder (PGD/PCBD).